The Role of Local Marginalization In Batam Island As An Industrial City In The Border Area of Indonesia - Fitrisia Munir; Artha Yudilla; Delmira Syafrini (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
Globalization has an open opportunity for border areas and periphery as a part of the center of industrial cities in Indonesia's development. Collaboration between Indonesia (Riau Island), Malaysia, and Singapore at border areas has involved developed countries with the high support of globalization, so currents have affected the urban system and destroyed many developed traditional regional models. This study aims to evaluate the marginalization of border communities and analyze their participation in sustainable development on Batam Island as an industrial city that is developing between countries. The research applied a descriptive qualitative research method with a case study approach. It used the concept of gentrification as an implication of a new industrial city, describing a phenomenon empirically. The findings show that Batam Island is one of the developing new industrial cities than other cities as a port for international activities in the border area and a high rush of people coming from outside the city to work and settle there. This research concludes that industrial city development strategies in the border area were needed and planned under a more macroscopic framework, for border communities are not deeply marginalized, and as part of modernization, industrial city growth.